Actinic keratosis: correlation between clinical and histological classification systems. (8th March 2016) - Schmitz, L.; Kahl, P.; Majores, M.; Bierhoff, E.; Stockfleth, E.; Dirschka, T.
Abstract: Background: There are several clinical and histological classification systems for grading actinic keratosis (AK) lesions. The Olsen clinical classification scheme grades AK lesions according to their thickness and degree of hyperkeratosis (grades 1–3). The Roewert‐Huber histological classification system grades AK lesions based on the extent of epidermal atypical keratinocytes (AK I–III). Objective: The aim of this study was to determine whether there is a correlation between these clinical and histological AK classification schemes. Methods: One AK lesion from patients in three pivotal clinical studies and routine practice was assessed clinically and histologically. A match in grading was defined as Olsen grade 1 being classified histologically as AK I, Olsen grade 2 as AK II and Olsen grade 3 as AK III. Results: Of the 892 lesions included, 29.0% were classified as Olsen grade 1, 59.6% as Olsen grade 2 and 11.3% as Olsen grade 3; 19.2% were histologically classified as AK I, 69.6% as AK II and 11.2% as AK III. Only 480 lesions (53.8%) had a matching clinical and histological classification. Of these matches, most were 'Olsen grade 2 = AK II' (83.1%). The Spearman's rank correlation coefficient for clinical and histological classification was r = 0.0499 ( P = 0.137). Conclusions: Clinical classification of AK lesions using the system of Olsen does not accurately match histological classification of the same lesions using the system of Roewert‐Huber. Consequently, it is not possible to draw conclusions about the histology of AK lesions from their clinical appearance. This finding reinforces the need to treat all AK lesions as well as field cancerization.